Art and craft of episiotomy - Patil, Gayatri L.; Pujar, Tejaswi V.; A. S., Sridevi; Priya, Edamadaka Vishnu; B. K., Sridevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Episiotomy is the most common obstetric surgical procedure performed in labor room. Mediolateral and Midline episiotomies are the most common types. Post-delivery suture angle is the most important determinant factor which predicts the risk of anal sphincter injuries. Mediolateral episiotomy has a significantly lower risk of OASIS rate when compared to midline episiotomies. Aim of the study was to know whether mediolateral episiotomies are actually mediolateral and does the angle of episiotomy influences the risk of anal sphincter injuries, maternal/fetal complications in the perinatal period. Methods: An observational study was conducted on 250 postpartum patients admitted to our hospital. Details of episiotomy in relation to incision angle, length, depth and post suturing angle were noted within two days of delivery. Results: Among the subjects included there were 40.8 % incisions were RMLE, average length was 3.32cms, average suture angle is 28.69 degree. OASIS was seen in 19.5% cases more so with midline episiotomies. Conclusions: Episiotomy is an essential, must to know skill. Compulsory ssupervised clinical teaching and use of skill lab training can prevent potential detrimental consequences.